Profissionalismo, gênero e subjetividades na justiça paulista - Benedito, Camila de Pieri (2013)
This research has as its objective, by the utilization of the concept of professionalism, the analysis of the impact of the growing female participation on juridical careers over subjectivities and identitary negotiations. The chosen methodology is based on semistructured, in depth interviews with: two female judges, one male judge, one male prosecutor and two public defenders, all from the town of Rio das Pedras (fictional name), situated on the country side of São Paulo. Professionalism, as understood especially through the views of Eliot Freidson (1996) and Julia Evetts (2006), contributes to the analysis of why some careers provide more opening than others to the numerical growth of women on their ranks. It is also useful when thought as discourse to observe the subjective negotiations between lawyers when constructing their perceptions about the careers they are part of. The central hypothesis is that as professionalism gets consolidated, the flexibility to female participation grows. Gender, understood as performatic by Judith Butler (2002) on her contributions get interspersed with professionalism, constructing identities and subjectivities that agree with the careers discourse.